The Relationship between Environmental Sanitation and the Incidence of Stunting in Toddlers - Sarita Tae; Wanti Wanti; Albina Bare Telan; Irwan Budiana; Muhammad Satria Mandala Pua Upa; Irfan Irfan (CV. Global Health Science Group, 2025)
Stunting is a condition of growth failure in infants (0-11 months) and toddlers (12-59 months) due to chronic malnutrition, especially during the first 1,000 days of life, resulting in children being too short for their age. Poor environmental sanitation can cause infectious diseases in toddlers, which can disrupt the digestive process in nutrient absorption and may lead to long-term stunting. The aim of this study is to determine the relationship between environmental sanitation factors and the incidence of stunting in toddlers. This observational analytical study used a case-control approach. The sample consisted of toddlers living in the Liliba Sub-district, totaling 74 toddlers: 37 cases (stunted) and 37 controls (not stunted). The research variables were wastewater management, availability of latrines, and handwashing habits. Data were collected by interview using questionnaire. The analytical test that will be used is the chi-square test. Data analysis was conducted using the chi-square test. The research results indicate a significant relationship between wastewater management (p=0.011), availability of toilets (p=0.040), and handwashing habits (p=0.011) with the incidence of stunting. Given the link between household wastewater management, toilet availability, handwashing habits, and the occurrence of stunting.